Innovation intermediaries revised: a systematic literature review on innovation intermediaries' role for knowledge sharing - Daniel Feser (Review of Managerial Science, 2022)
The decision to collaborate for companies in knowledge exchange processes has become more complex due to a greater diversity of innovation intermediaries from companies, universities, government and societal actors. The aim of this study is to uncover and conceptualize the role of innovation intermediaries in knowledge sharing. Specifically in tacit knowledge sharing, intermediaries function as boundary spanners between various stakeholders in the innovation process. Despite this potential, which has been discussed in a large strand of case studies, there is no comprehensive concept to determine factors that influence innovation intermediaries in knowledge sharing. This paper develops an analytical framework of innovation intermediaries for prospective empirical work building on factors influencing innovation intermediaries in knowledge sharing by systematically reviewing related literature. It specifically presents what are the determinants, factors and indicators discussed empirically innovation intermediaries in knowledge sharing. The first results is that the measurement of innovative outcome intermediaries enables a broader perspective in comparison to traditional innovation indicators. The second results that literature discusses indirect innovation that enhances clients' innovative capabilities and their entrepreneurial activities. The third results demonstrates, that while the internal perspective varies with the heterogeneous actors, the development of contextual knowledge of intermediaries in networks and its transfer is central for empirical analysis. The conceptualization of this framework paves the path for further research needed to uncover the role of intermediaries.
Keywords: 650; Innovation intermediaries; Knowledge-sharing; Systematic literature review; Innovation systems